2021
DOI: 10.36660/abc.20200371
|View full text |Cite
|
Sign up to set email alerts
|

Síndrome de Heyde: Estratégias Terapêuticas e Seguimento de Longo Prazo

Abstract: Fundamentos: A síndrome de Heyde é a associação de estenose aórtica importante com episódio de sangramento gastrointestinal por lesões angiodisplásicas. Pouco é conhecido sobre os fatores associados a novos sangramentos e desfechos em longo prazo. Além disso, a maioria dos dados é restrita a relatos de casos e pequenas séries. Objetivo: Avaliar o perfil clínico, laboratorial e ecocardiográfico de pacientes com síndrome de Heyde submetidos a intervenção valvar ou tratamento medicamentoso. Métodos: Coorte prospe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…A small prospective study reported that SAVR also effectively reduces gastrointestinal bleeding in these patients. 37…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A small prospective study reported that SAVR also effectively reduces gastrointestinal bleeding in these patients. 37…”
Section: Discussionmentioning
confidence: 99%
“…A small prospective study reported that SAVR also effectively reduces gastrointestinal bleeding in these patients. 37 An evident strength of our study is that our cohort consisted of patients who were part of a prospective registry. 15 The registry captured all AS patients necessitating TAVI since the introduction of the procedure in our center in 2008 and allowed us to have an extended follow-up.…”
Section: Figure 3 Gastrointestinal Bleeding (Gib) Episodes Before And...mentioning
confidence: 99%